2019
DOI: 10.1016/j.scitotenv.2019.04.105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brownification and warming on algal blooms, metabolism and higher trophic levels in productive shallow lake mesocosms

Abstract: Effects of brownification and warming on algal blooms, metabolism and higher trophic levels in productive shallow lake mesocosms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 79 publications
2
22
0
Order By: Relevance
“…This is in the upper range of the predicted increase in temperatures under RCP 8.5 predictions (2.6–4.8°C, IPCC, ) and complements other mesocosm climate warming experiments (e.g. Feuchtmayr et al, ; Feuchtmayr et al, ; Urrutia‐Cordera et al, ; Yvon‐Durocher et al, ).…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…This is in the upper range of the predicted increase in temperatures under RCP 8.5 predictions (2.6–4.8°C, IPCC, ) and complements other mesocosm climate warming experiments (e.g. Feuchtmayr et al, ; Feuchtmayr et al, ; Urrutia‐Cordera et al, ; Yvon‐Durocher et al, ).…”
Section: Methodssupporting
confidence: 81%
“…Sampling occurred every 4 weeks as well as additional sampling which occurred on the day of flushing (post-flushing), and 1 week after a flushing event before returning to a four-weekly schedule 8.5 predictions (2.6-4.8°C, IPCC, 2013) and complements other mesocosm climate warming experiments (e.g. Feuchtmayr et al, 2009;Feuchtmayr et al, 2019;Urrutia-Cordera et al, 2017;Yvon-Durocher et al, 2015).…”
Section: Warmingmentioning
confidence: 99%
“…In agreement with our model predictions, cyanobacterial abundance was lowest in blue lakes and highest in green and murky lakes. Other studies have also shown that lake browning may result in the loss of diatoms and green algae (Urrutia‐Cordero et al ), while it tends to favor cyanobacteria (Ekvall et al , Lebret et al , Feuchtmayr et al ) and cryptophytes (Deininger et al , Urrutia‐Cordero et al , Wilken et al ). These patterns are supported by recent competition experiments that, similar to our results, revealed that the common bloom‐forming cyanobacterium Microcystis aeruginosa lost the competition from a green alga in blue light, but won in orange‐red light (Tan et al ).…”
Section: Discussionmentioning
confidence: 98%
“…DOM is also generated within lakes and reservoirs via photosynthesis (production of algal exudates and release via cell lysis) and through processing of particulate matter (Tranvik et al, 2009) so that DOM concentrations at the point of abstraction from reservoirs represent the sum of these removal and generation processes. Importantly, in-reservoir algal production, and hence within-reservoir generation of DOM is often limited by the availability 350 of either phosphorus, nitrogen or both, so that waterbodies receiving high levels of inorganic nutrient inputs, either externally from their catchments or internally from sediments, are likely to generate additional DOM within the water column (Feuchtmayr et al, 2019;Evans et al, 2017a). DOM produced via these processes is relatively transparent and hydrophilic in comparison with DOM generated by organic rich soils, and thus presents different challenges for treatment, particularly as the hydrophilic DOM is not easily removed through coagulation (Matilainen et al, 2010) and may lead to the need for additional capital investment in order to effectively reduce residual DOM in drinking water.…”
Section: In-lake Cycling Of Dissolved Organic Matter 335mentioning
confidence: 99%